LCA applied to nano scale zero valent iron synthesis - Martins, Florinda (2019)
Purpose Application of zero valent iron nanoparticles is an innovative technology for ground water treatment and soil remediation. There are several methods to synthesise nano scale zero valent iron (nZVI), namely through bottom-up methods which consists on chemical reactions using strong reducing agents. In this work, the environmental impacts and costs were determined for two methods, namely the traditional one that uses sodium borohydride and the green method that uses extracts obtained from natural products. Methods The consideration of environment and economic aspects in the earlier stages of the synthesis processes and in the development of new materials is of great importance since it can help to decide if alternative methods are promising and should be further developed aiming more sustainable processes. In this work, life cycle assessment (LCA) was used as an ecodesign strategy evaluating environmental performance of the two synthesis methods, identifying critical stages of the synthesis processes of nZVI. An economic evaluation and a sensitivity analysis considering a different scenario for electricity production were also performed. Results and discussion The results obtained in this study showed that the green synthesis method presents lower environmental impacts than the traditional one, roughly 50% lower in the first scenario. In the second scenario, environmental impact of green synthesis corresponds to 38% of the environmental impact of traditional synthesis. In the green method, the critical stage is the extraction process which is closely related to the electricity production. In the traditional method, the reactant use is the critical stage that is related to the production of sodium borohydride. The economic evaluation indicated that the traditional synthesis method is much more expensive than the green synthesis (roughly eight times higher). Conclusions From the results obtained, it is possible to conclude that the green synthesis method presents lower environmental impacts in both scenarios and lower costs than the traditional synthesis.